Genetically-targeted photorelease of endocannabinoids enables optical control of GPR55 in pancreatic β-cells. Issue 40 (27th September 2021) - Tobias, Janelle M.; Rajic, Gabriela; Viray, Alexander E. G.; Icka-Araki, David; Frank, James A.
Abstract : Optically-cleavable targeted ligands unite photocaged chemistry with genetic targeting to induce cell activity at defined membranes. OCT-PEA uncaging stiumlates β-cell activity via cell surface GPR55. Abstract : Fatty acid amides (FAAs) are a family of second-messenger lipids that target cannabinoid receptors, and are known mediators of glucose-stimulated insulin secretion from pancreatic β-cells. Due to the diversity observed in FAA structure and pharmacology, coupled with the expression of at least 3 different cannabinoid G protein-coupled receptors in primary and model β-cells, our understanding of their role is limited by our inability to control their actions in time and space. To investigate the mechanisms by which FAAs regulate β-cell excitability, we developed the Optically-Cleavable Targeted (OCT)-ligand approach, which combines the spatial resolution of self-labeling protein (SNAP-) tags with the temporal control of photocaged ligands. By linking a photocaged FAA to an o -benzylguanine (BG) motif, FAA signalling can be directed towards genetically-defined cellular membranes. We designed a probe to release palmitoylethanolamide (PEA), a GPR55 agonist known to stimulate glucose-stimulated insulin secretion (GSIS). When applied to β-cells, OCT-PEA revealed that plasma membrane GPR55 stimulates β-cell Ca 2+ activity via phospholipase C. Moving forward, the OCT-ligand approach can be translated to other ligands and receptors, and will open up new experimental possibilities in targeted pharmacology.